CONTROL OVER «BRUSH-COMMUTATOR» SPARKING IN DC MACHINES USING OPTOELECTRONIC SPARKING ANALYZER - V. Zelinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A «brush-commutator» contact is one of the factor that affects commutative properties and commutation. The paper presents a new method for estimation of a commutation. It is based not on the researchers’ experience but on the corresponding indicated values of a computer optoelectronic sparking analyzer. This analyzer permits to identify specific commutator sectors and its circuits at an inequality angle of every individual sector, rotation rate, time selection of measuring cycle, sparking estimation of separate commutator sectors and every sector of subsequent measuring cycle.